The Job Characteristics Theory: A Review - - Faturochman (Buletin Psikologi, 1997)
Many scholars have argued that one way to increase employee performance and personal outcomes is by enriching the job. Both employee performance and personal outcomes, especially satisfaction, can be improved through job enrichment by giving greater opportunity to the individual for developing personal achievement.